PROFESSIONAL EXAMINATIONS. - Chamberlain, Henry T.; Chamberlain, John H.; Mautz, R. K. (The Accounting Review, 1958)
The article presents various problems prepared by the Board of Examiners of the American Institute of Certified Public Accountants, U.S. and presented as the first half of the Certified Public Accountants (C.P.A.) examination in accounting practice May 14, 1958. The candidates were required to solve problems one, two and three and either problem four or problem five. The total weight assigned to this section of the examination was 50 points and the examiners point out that the suggested time allowances given below are approximately proportional to the point value of the various problems. The time allowed for this section of the examination was four and a half hours. The article also includes two groups of questions presented in the audit section of the May 15, 1958 Uniform C.P.A. Examination. The estimated time allowances are approximately proportional to the point value of the problems, the total of which for this examination is 100.